Association between individual urinary iodine concentrations in pregnant women and maternal/newborn outcomes - Bolfi, Fernanda [UNESP]; Marum, Maryan Borcsik [UNESP]; Fonseca, Samantha Ellen da Silva [UNESP]; Mazeto, Glaucia M F S. [UNESP]; Nogueira, Celia Regina [UNESP]; Nunes-Nogueira, Vania Dos Santos [UNESP] (Bioscientifica, 2025)
Objective: To assess whether individual diagnosis of low urinary iodine concentration (UIC) in pregnant women is associated with adverse maternal and neonatal outcomes. Methods: Studies that compared pregnant women with UIC <150 μg/L and those with UIC 150–249 μg/L were systematically reviewed. MEDLINE, Embase, LILACS and CENTRAL were our source databases. Selection of studies, risk-of-bias assessment and data extraction were performed in pairs and independently. Relative risk (RR) with 95% confidence interval (CI) was calculated as an estimate of the effect of iodine <150 μg/L. Stata software was used to perform meta-analyses. The quality of evidence was determined according to the Grading of Recommendations Assessment, Development and Evaluation. Results: In total, 7000 studies were identified, of which 63 were included. With low or very low certainty of the evidence, no difference in the incidence of miscarriage (RR: 0.87, 95% CI: 0.64–1.18, 6 studies, 4855 participants), maternal hypothyroidism (RR: 1.05, 95% CI: 0.68–1.60, 10 studies, 11,773 participants), preterm birth (RR: 1.20, 95% CI: 0.97–1.48, 13 studies, 15,644 participants), stillbirths (RR: 0.79, 95% CI: 0.34–1.82, 6 studies, 3406 participants), low birth weight (RR: 1.25, 95% CI: 0.88–1.78, 10 studies, 10,775 participants) and small for gestational age (RR: 1.11, 95% CI: 0.90–1.37, 5 studies, 4266 participants) was observed between the two groups. Conclusion: In pregnant women, individual diagnosis of UIC <150 μg/L was not associated with adverse maternal and neonatal outcomes, emphasizing UIC as a limited method to assess individual iodine status during pregnancy.
Keywords: iodine; meta-analysis; pregnancy; systematic review; urine